Lithium ion battery electrolyte and application thereof

By introducing single-ion conductors and film-forming additives into the lithium-ion electrolyte, the lithium-ion transference number is increased, and a stable SEI film is formed, which solves the problem of the difficulty in balancing fast charging and high-temperature performance of lithium-ion batteries and improves the fast charging and high-temperature cycling performance of the battery.

CN117477031BActive Publication Date: 2026-11-06ENVISION RUITAI DYNAMICS TECH (SHANGHAI) CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311520408.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-14
Publication Date
2026-11-06
Estimated Expiration
2043-11-14

AI Technical Summary

Technical Problem

Existing lithium-ion batteries struggle to balance fast charging capability and high-temperature performance. Commonly used solvents cannot simultaneously meet the requirements of low viscosity and low side reactions, and reducing film-forming additives can lead to an increase in side reactions.

Method used

A lithium-ion electrolyte containing single-ion conductor additives and film-forming additives is used. The single-ion conductor additives increase the lithium-ion transference number and form a stable solid electrolyte interface film, while the film-forming additives suppress side reactions on the electrode surface and optimize the composition of the SEI film.

Benefits of technology

It improves the fast charging and rate performance of lithium-ion batteries, reduces lithium-ion concentration polarization on the surface of the negative electrode, and enhances high-temperature cycle performance and initial discharge capacity, thus solving the problem of balancing fast charging and high-temperature performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117477031B_ABST
    Figure CN117477031B_ABST
Patent Text Reader

Abstract

This invention proposes a lithium-ion battery electrolyte and its application. The electrolyte comprises at least: a non-aqueous solvent; a lithium salt; and additives, including a single-ion conductor additive with the general structural formula: where n = 10 to 100. The lithium-ion battery electrolyte and its application proposed in this invention can improve the fast-charging and rate performance of lithium-ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of power battery technology, specifically to a lithium-ion battery electrolyte and its application. Background Technology

[0002] With the promotion and popularization of electric vehicles, people's demands for fast charging capabilities are increasing, posing new challenges to the fast charging capabilities of lithium-ion batteries. In lithium-ion batteries, the electrolyte plays a crucial role in ion transport. The electrolyte's ability to conduct lithium ions and the speed at which lithium ions migrate from the electrolyte to the negative electrode surface after desolvation have a critical impact on the battery's fast charging capability. To improve the fast charging capability of the electrolyte, the industry generally optimizes the electrolyte formulation based on the two aforementioned kinetic processes, including but not limited to using solvents with lower viscosity, solvents with lower lithium-ion solvation capabilities, and reducing the use of film-forming additives. However, commonly used solvents may not simultaneously meet the requirements of the first two conditions, and reducing the amount of film-forming additives can also lead to an increase in side reactions. Summary of the Invention

[0003] This invention proposes a lithium-ion battery electrolyte and its application. The lithium-ion battery electrolyte and its application provided by this invention can improve the fast charging and rate performance of batteries, and effectively solve the problem of the difficulty in balancing fast charging capability and high-temperature performance.

[0004] To solve the above-mentioned technical problems, the present invention provides a lithium-ion battery electrolyte, comprising at least the following components: a non-aqueous solvent;

[0005] Lithium salts; and

[0006] Additives, including single-ion conductor additives, wherein the general structural formula of the single-ion conductor additives is:

[0007] Where n = 10 to 100.

[0008] In one embodiment of the present invention, the mass content of the single-ion conductor additive in the electrolyte is 0.05%-3%.

[0009] In one embodiment of the present invention, the additive further includes a film-forming additive, which includes one or a combination of at least two of vinyl sulfate, 1,3-propanesulfonate lactone, vinylene carbonate, fluoroethylene carbonate, or ethylene ethylene carbonate.

[0010] In one embodiment of the present invention, the film-forming additive has a mass content of 0.5%-2% in the electrolyte.

[0011] In one embodiment of the present invention, the film-forming additive includes vinyl sulfate and 1,3-propanesulfonate lactone.

[0012] In one embodiment of the present invention, the lithium salt is selected from any one or a combination of at least two of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalate-borate), lithium difluorobis(oxalate-phosphate), lithium difluorophosphate, or lithium trifluoromethanesulfonate.

[0013] In one embodiment of the present invention, the lithium salt in the electrolyte has a mass content of 8%-18%.

[0014] In one embodiment of the present invention, the non-aqueous solvent includes any one or a combination of at least two of ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, or diethyl carbonate, and the mass content of the non-aqueous solvent in the electrolyte is 60%-85%.

[0015] The present invention also provides a lithium-ion battery, comprising the lithium-ion battery electrolyte described above.

[0016] The present invention also provides an electronic device comprising the lithium-ion battery described above.

[0017] In summary, this invention proposes a lithium-ion battery electrolyte and its application. The single-ion conductor additive can increase the lithium-ion transport number of the electrolyte, enhance lithium-ion transport capacity, and significantly reduce lithium-ion concentration polarization on the negative electrode surface, effectively alleviating the lithium deposition problem on the negative electrode surface during fast charging. The single-ion conductor additive forms a stable solid electrolyte interface film on the negative electrode surface, promoting the desolvation process of lithium ions, improving the battery's fast charging and rate performance, and effectively solving the problem of balancing fast charging capability and high-temperature performance. The film-forming additive can suppress the occurrence of side reactions on the electrode surface, increase the initial discharge capacity of the lithium-ion battery, improve the high and low temperature storage performance of the lithium-ion battery, and enhance the high-temperature cycle performance of the lithium-ion battery. Detailed Implementation

[0018] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention.

[0019] It should be understood that the invention can be embodied in various forms and should not be construed as being limited to the embodiments set forth herein. Rather, providing these embodiments will make the disclosure thorough and complete, and will fully convey the scope of the invention to those skilled in the art.

[0020] The technical solution of the present invention will be further described in detail below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0021] This invention proposes a lithium-ion battery electrolyte, comprising at least a non-aqueous solvent, a lithium salt, and additives, wherein the additives include single-ion conductor additives, and the general structural formula of the single-ion conductor additives is:

[0022] Where n = 10 to 100. In this embodiment, the mass content of the single-ion conductor additive in the electrolyte is, for example, 0.05%-3%. By introducing a soluble single-ion conductor as an additive into the electrolyte, the lithium-ion transference number of the electrolyte is increased. Without a significant change in the conductivity of the electrolyte, the increase in the lithium-ion transference number enhances the lithium-ion transport capacity, significantly reduces the lithium-ion concentration polarization on the surface of the negative electrode, and effectively alleviates the lithium deposition problem on the surface of the negative electrode during fast charging. In addition, the single-ion conductor additive can also form a stable solid electrolyte interface (SEI) film on the surface of the negative electrode, promoting the desolvation process of lithium ions. The electrolyte containing this single-ion conductor additive can effectively solve the problem of the difficulty in simultaneously achieving fast charging capability and high-temperature performance of the battery.

[0023] In one embodiment of the present invention, when the lithium-ion transport number of the electrolyte is low, a lithium-ion concentration gradient will form on the surface of the negative electrode, leading to concentration polarization and easily causing lithium plating. The reason for the low lithium-ion transport number is that lithium ions have a small radius and high charge density, making them easy to form coordination structures with the solvent, i.e., the solvated sheath. Therefore, lithium-ion transport is actually a process of migration of lithium-ion clusters surrounded by multiple solvent molecules. These clusters have a large radius and high intermolecular friction, so their migration is slow. Conversely, anions have a large radius and low charge density, making them difficult to solvate and form clusters, thus their migration is faster. Therefore, the key to improving the lithium-ion transport number is to break the lithium-ion solvated clusters and block the transport of anions. The single-ion conductor additive provided in this application is a single-ion conductor type soluble polymer additive with a high density of sulfonic acid groups. As negative charge centers, the sulfonic acid groups can interact electrostatically with solvated lithium ions, removing lithium ions from the solvated sheath and promoting the hopping conduction of lithium ions between negative charge centers. Simultaneously, the negatively charged centers will generate electrostatic repulsion towards the anions, hindering their movement. Therefore, single-ion conductor additives can significantly increase the lithium-ion transport number of the electrolyte, improving the battery's fast-charging and rate performance without affecting its high-temperature performance.

[0024] In one embodiment of the present invention, the additive further includes a film-forming additive, which includes one or a combination of at least two of the following: ethylene sulfate (DTD), 1,3-propanesultone (PS), vinylene carbonate (VC), fluoroethylene carbonate (FEC), or vinyl ethylene carbonate (VEC). The film-forming additive has a mass content of, for example, 0.5%-3% in the electrolyte. In this embodiment, the film-forming additive includes, for example, at least ethylene sulfate and 1,3-propanesultone, which can optimize the SEI film composition, form a stable and dense SEI film, suppress the occurrence of side reactions on the electrode surface, increase the initial discharge capacity of the lithium-ion battery, improve the high and low temperature storage performance of the lithium-ion battery, and enhance the high-temperature cycle performance of the lithium-ion battery.

[0025] In one embodiment of the present invention, the lithium salt includes, for example, any one or a combination of at least two of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(oxalato)borate (LiBOB), lithium difluorobis(oxalato)phosphate (LiDODFP), lithium difluorophosphate (LiDFP), or lithium trifluoromethanesulfonate (CF3SO3Li). In this embodiment, the mass content of the lithium salt in the electrolyte is 8%-18%.

[0026] In one embodiment of the present invention, the non-aqueous solvent includes any one or a combination of at least two of ethylene carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), propylene carbonate (PC), or diethyl carbonate (DEC). In one embodiment of the present invention, the mass percentage of the non-aqueous solvent in the electrolyte is, for example, 60%-85%. In this embodiment, the non-aqueous solvent includes, for example, battery-grade ethylene carbonate, ethyl methyl carbonate, and diethyl carbonate, and the mass ratio of ethylene carbonate, ethyl methyl carbonate, and diethyl carbonate is 3:5:5. By controlling the content of the non-aqueous solvent, while maintaining the performance of the electrolyte, it is possible to prevent excessively high non-aqueous solvent content, which could lead to excessively high electrolyte viscosity and consequently reduced ionic conductivity and wettability of the electrolyte.

[0027] In one embodiment of the present invention, when preparing the electrolyte, the content of stable gases such as nitrogen or argon in the glove box is 99.999%, the actual oxygen content in the glove box is less than or equal to 0.1 ppm, and the moisture content is less than or equal to 0.1 ppm. After the non-aqueous solvent is mixed evenly according to the mass ratio, the fully dried lithium salt is added to the non-aqueous solvent, and additives are added to prepare the non-aqueous electrolyte for lithium-ion batteries. The contents of each component other than the non-aqueous solvent are weight percentages calculated based on the total weight of the electrolyte.

[0028] This invention also proposes a lithium-ion battery, comprising a positive electrode, a separator, a negative electrode, and an electrolyte. The separator is located between the positive and negative electrodes, and the electrolyte is filled between the positive electrode, the separator, and the negative electrode. The electrolyte is the lithium-ion battery electrolyte described above. The lithium-ion battery can be, for example, a primary battery or a secondary battery. A secondary battery can be, for example, a pouch battery, a hard-case battery, or a cylindrical battery. This invention does not specifically limit the type or category of lithium-ion batteries.

[0029] In one embodiment of the present invention, the positive electrode sheet includes a positive current collector and a positive active layer coated on at least one surface of the positive current collector. The positive current collector is, for example, a foil formed by surface treatment of materials such as nickel, titanium, aluminum, silver, stainless steel, or carbon. Besides foil, the positive current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam, or non-woven fabric. The thickness of the positive current collector is, for example, 8 μm-15 μm. In this embodiment, the positive current collector is, for example, an aluminum foil, and the thickness of the aluminum foil is, for example, 13 μm.

[0030] In one embodiment of the present invention, the positive electrode active layer includes a positive electrode active material, a binder, and a conductive agent. The positive electrode active material can be any positive electrode active material used in lithium-ion secondary batteries; that is, compounds capable of reversible lithium-ion intercalation and deintercalation can be used. In one embodiment of the present invention, the positive electrode active material is, for example, Li. x MO2 or Li y M₂O₄ represents lithium-containing complex oxides, spinel-like oxides, layered metal chalcogenides, or olivine structures, where M is a transition metal, 0 ≤ x ≤ 1, 0 ≤ y ≤ 2. Specifically, examples include lithium cobalt oxides such as LiCoO₂, lithium manganese oxides such as LiMn₂O₄, lithium nickel oxides such as LiNiO₂, and Li... 4 / 3 Ti 5 / 3lithium-titanium oxides such as O4, lithium-manganese-nickel composite oxides, or lithium-manganese-nickel-cobalt composite oxides. In another embodiment of the present invention, the positive electrode active material may also be, for example, a material with an olivine-type crystal structure such as LiMPO4, where M is selected from Fe, Mn, Ni, and the like. In another embodiment of the present invention, the positive electrode active material employs, for example, a lithium-containing composite oxide with a layered structure or a spinel structure, such as LiCoO2, LiMn2O4, LiNiO2, or LiNi 1 / 2 Mn 1 / 2 O2 and other lithium-manganese-nickel composite oxides, and for example, Li m Ni x Mn y Co 1-x-y O2 and other lithium-manganese-nickel-cobalt composite oxides, where 0.9<m<1.1, 0.4≤x≤0.95, 0<y≤0.3. In the present invention, one type of positive electrode active material may be used alone, or two or more types may be used in combination. For example, by simultaneously using a lithium-containing composite oxide with a layered structure and a lithium-containing composite oxide with a spinel structure, both high capacity and improved safety can be achieved. In this embodiment, the positive electrode active material is, for example, LiNi 0.6 Co 0.1 Mn 0.3 O2.

[0031] In an embodiment of the present invention, the binder is, for example, selected from any one or more of polyvinylidene fluoride (PVDF), poly(ethylene oxide) (PEO), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinyl ether, polymethyl methacrylate (PMMA), ethylene-propylene-diene terpolymer (EPDM), polyhexafluoropropylene, or polymerized styrene butadiene rubber (SBR). The conductive agent is, for example, selected from any one or more of conductive carbon black (Super P), acetylene black, carbon nanotubes, graphene, and the like.

[0032] In an embodiment of the present invention, the positive electrode active material is, for example, LiNi 0.6 Co 0.1 Mn 0.3O2, a binder such as polyvinylidene fluoride, and a conductive agent such as conductive carbon black are used. The positive electrode active material, conductive agent, and binder are mixed in a mass ratio of 98:1:1, and an organic solvent is added. The mixture is stirred under vacuum until the system is homogeneous to obtain a positive electrode slurry. The organic solvent is, for example, N-methylpyrrolidone (NMP). The positive electrode slurry is uniformly coated onto aluminum foil, then air-dried at room temperature and transferred to an oven for drying. After cold pressing and slitting, the positive electrode sheet is obtained. In other embodiments, the positive electrode sheet can also be obtained by any other electrode forming method.

[0033] In one embodiment of the present invention, the negative electrode sheet includes, for example, a negative current collector and a negative active layer coated at least on one surface of the negative current collector. The negative current collector is selected from, for example, a copper foil current collector, a composite copper foil current collector, a carbon current collector, a foamed copper current collector, or a stainless steel current collector, and the thickness of the negative current collector is, for example, 8 μm-15 μm. In this embodiment, the negative current collector is, for example, copper foil, and the thickness of the copper foil is, for example, 13 μm.

[0034] In one embodiment of the present invention, the negative electrode active layer includes a negative electrode active material, a conductive agent, a binder, and a thickener. The negative electrode active material is selected from compounds capable of intercalating and deintercalating lithium ions. In one embodiment of the present invention, it is, for example, an alloy or oxide of aluminum, silicon, or tin, or various materials such as carbon materials. The oxide is, for example, titanium dioxide, and the carbon material is, for example, graphite, pyrolytic carbon, coke, glassy carbon, sintered organic polymer compounds, or mesophase carbon microspheres.

[0035] In one embodiment of the present invention, the adhesive is selected from one or more of polyvinylidene fluoride, polyethylene oxide, polyamide, polypropylene, polyacrylate, polyethylene ether, polymethyl methacrylate, polyhexane, or styrene-butadiene rubber. The thickener is selected from, for example, sodium carboxymethyl cellulose (CNC-Na), and the conductive agent is selected from one or more of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, and graphene.

[0036] In one embodiment of the present invention, the negative electrode current collector is selected, for example, from copper foil; the negative electrode active material is selected, for example, from artificial graphite; the conductive agent is selected, for example, from conductive carbon black; the thickener is selected, for example, from sodium carboxymethyl cellulose; and the binder is selected, for example, from styrene-butadiene rubber. In one embodiment of the present invention, artificial graphite, conductive agent, binder, and thickener carbon are mixed in a mass ratio of 96:1:1:2, added to a deionized water solvent, and stirred evenly under vacuum to obtain a negative electrode slurry. The negative electrode slurry is coated onto copper foil, then air-dried at room temperature and transferred to an oven for drying. After cold pressing and slitting, the negative electrode sheet is obtained. In other embodiments, the negative electrode sheet can also be obtained by any other electrode forming method.

[0037] In one embodiment of the present invention, the separator is, for example, a polyethylene (PE) membrane, a polypropylene (PP) membrane, a glass fiber membrane, a polyethylene membrane, or a composite membrane. The thickness of the separator is, for example, 9μm-15μm. In one embodiment of the present invention, the above-mentioned positive electrode, separator, and negative electrode are placed sequentially, with the separator positioned between the positive and negative electrode to act as a separator. A bare battery cell is obtained by winding or stacking the cells. The bare battery cell is then placed in an aluminum-plastic film, dried in a vacuum oven at 120°C, and injected with the prepared electrolyte at a rate of 3.0 g / Ah. After sealing, the cell undergoes processes such as settling, hot and cold pressing, formation, clamping, and capacity testing to obtain a 1Ah soft-pack lithium-ion secondary battery.

[0038] The present invention will be explained in more detail below by referring to embodiments, which should not be construed as limiting. Appropriate modifications can be made within the scope of the present invention, and all such modifications fall within the technical scope of the present invention.

[0039] Example 1

[0040] Electrolyte preparation: In an argon-filled glove box, with a stable gas content of 99.999% (nitrogen or argon), an actual oxygen content of less than 0.1 ppm, and a moisture content of less than 0.1 ppm, battery-grade ethylene carbonate, ethyl methyl carbonate, and diethyl carbonate are mixed uniformly at a mass ratio of 3:5:5. Based on a total electrolyte mass of 100%, the lithium salt in the electrolyte is LiPF6, with a LiPF6 mass content of 13%. The degree of polymerization (n) of the single-ion conductor additive is 10, and the added mass content is 0.5%. The film-forming additives are vinyl sulfate and 1,3-propanesulfonate lactone, with vinyl sulfate and 1,3-propanesulfonate lactone each having a mass content of 0.5%.

[0041] Preparation of positive electrode: LiNi 0.6 Co 0.1 Mn 0.3O2, polyvinylidene fluoride, and conductive carbon black were mixed in a mass ratio of 98:1:1, and N-methylpyrrolidone was added. The mixture was stirred under vacuum until the system was homogeneous to obtain a positive electrode slurry. The positive electrode slurry was uniformly coated onto aluminum foil, then air-dried at room temperature and transferred to an oven for drying. After cold pressing and slitting, the positive electrode sheet was obtained.

[0042] Preparation of negative electrode sheet: Artificial graphite, conductive carbon black, sodium carboxymethyl cellulose, and styrene-butadiene rubber are mixed in a mass ratio of 96:1:1:2, added to deionized water, and stirred evenly under the action of a vacuum stirrer to obtain a negative electrode slurry. The negative electrode slurry is coated on copper foil, then dried at room temperature and transferred to an oven for drying. After cold pressing and slitting, the negative electrode sheet is obtained.

[0043] Selection of diaphragm: 10μm polypropylene film was selected as the diaphragm.

[0044] Battery fabrication: The positive electrode, separator, and negative electrode are stacked sequentially, with the separator positioned between the positive and negative electrodes to provide insulation. This stacking process yields a bare battery cell. The cell is then wrapped with an aluminum-plastic film, dried in a vacuum oven at 120°C, and injected with the prepared electrolyte at a rate of 3.0 g / Ah. The cell is then sealed to allow for electrolyte formation, resulting in a 1 Ah soft-pack lithium-ion secondary battery.

[0045] In this invention, Examples 2-5 and Comparative Examples 1-6 are also provided. The mass content of each component in the electrolyte of Examples 2-5 and Comparative Examples 1-6 is shown in Table 1. Other steps are the same as in Example 1 to obtain different finished soft-pack lithium-ion secondary batteries.

[0046] In this invention, lithium-ion batteries were prepared using different electrolyte ratios in Examples 1-5 and Comparative Examples 1-6, and the performance of the lithium-ion batteries was tested. The test results are shown in Table 2.

[0047] Table 1 shows the electrolyte formulations in Examples 1-5 and Comparative Examples 1-6.

[0048]

[0049] In one embodiment of the present invention, the lithium-ion transport number of the electrolyte is measured by chronoamperometry: a lithium-lithium symmetrical battery is assembled using a separator impregnated with the electrolyte; a polarization voltage of 5 mV is applied to the symmetrical battery; the polarization time is 3600 s; and the impedance before and after polarization is measured by AC impedance spectroscopy. The lithium-ion transport number t is calculated by the following formula: t = [I s (V-I0R 0) ] / [I0(VI s R s Where V is the polarization voltage, I...s and R s Let I0 and R0 be the stable current and interface impedance after polarization, respectively, and let I0 and R0 be the current and interface impedance before polarization, respectively.

[0050] In one embodiment of the present invention, the cyclic test is performed at a specified temperature, with a current of 1C within a specified voltage range of 2.8V-4.4V, and the discharge capacity of each cycle is recorded. The test ends when the battery capacity reaches 80% of the first cycle capacity (80% State of Health, 80% SOH).

[0051] In one embodiment of the present invention, the rate performance test involves discharging the battery cell at a specified temperature and with a specified C-rate current within a specified potential range of 2.8V-4.4V, and recording the retention rate of the cell's discharge capacity relative to the discharge capacity at a 0.33C current. In this embodiment, the specified C-rate is, for example, 4C.

[0052] In one embodiment of the present invention, the fast charging test uses fast charging cycles to measure the fast charging capability of the battery. The battery is subjected to fast charging cycle tests with charge and discharge regimes of 3-10% SOC 2C, 10-20% SOC 3C, 20-50% SOC 4C, 50-70% SOC 3C, 70-80% SOC 2C, and 80-97% SOC 1C. The discharge capacity of each cycle is recorded, and the test ends when the battery capacity reaches 80% of the capacity of the first cycle.

[0053] Table 2. Performance test results of lithium-ion batteries in Examples 1-5 and Comparative Examples 1-6

[0054]

[0055] Please refer to Tables 1 and 2. Comparing Examples 1-3 and Comparative Examples 1 and 6, it can be seen that as the mass content of the single-ion conductor additive increases, the lithium-ion transport number of the electrolyte also gradually increases, indicating that the single-ion conductor additive used in this invention can effectively improve the lithium-ion transport number. Specifically, in Example 1, compared to Comparative Example 1 without the single-ion conductor additive, the lithium-ion transport number is nearly doubled, indicating that the single-ion conductor additive can break the solvation sheath layer of lithium ions and improve lithium-ion transport. Furthermore, as the mass content of the single-ion conductor additive increases, the fast-charge cycle performance and rate performance of the lithium-ion battery show a trend of first increasing and then decreasing. This is because as the amount of single-ion conductor additive increases, the electrolyte viscosity also gradually increases, and eventually the overall battery performance reaches its peak at a certain dosage. Therefore, the mass content of the single-ion conductor additive in the electrolyte is 0.05%-3% to ensure that the overall battery performance does not deteriorate.

[0056] Please refer to Tables 1 and 2. Comparing Examples 2 and 4 and Comparative Examples 2-3, it can be seen that the degree of polymerization (n) of the single-ion conductor additive has a significant impact on the lithium-ion transference number and cell performance. When the polymerization degree is too low, the additive molecules move more easily in the electrolyte, making it more difficult to block anions, resulting in limited improvement in fast-charging cycle performance and rate performance. Conversely, when the polymerization degree is too high, the additive becomes insoluble. Therefore, controlling the degree of polymerization (n) of the single-ion conductor additive to 10–100 is crucial to ensure the overall performance of the lithium-ion battery.

[0057] Please refer to Tables 1 and 2. Comparing Examples 1-5 and Comparative Examples 1-6, it can be seen that in different lithium-ion batteries, the high-temperature cycle performance of lithium-ion batteries is at the same level regardless of the degree of polymerization, whether or not the single-ion conductor additive is added, and the amount added. This indicates that the single-ion conductor additive has no effect on the high-temperature performance of the battery, but can effectively improve the fast charging and rate performance of lithium-ion batteries, effectively solving the problem of the difficulty in balancing fast charging performance and high-temperature performance.

[0058] This invention also provides an electronic device comprising at least one of the aforementioned lithium-ion batteries, which provides electrical energy. The electronic device can be a vehicle, mobile phone, portable device, laptop computer, ship, spacecraft, electric toy, or power tool, etc. In one embodiment of this invention, the vehicle is, for example, a new energy vehicle, which can be a pure electric vehicle, a hybrid electric vehicle, or a range-extended electric vehicle, etc. Spacecraft include airplanes, rockets, space shuttles, and spacecraft, etc. Electric toys include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc. Power tools include metal cutting power tools, grinding power tools, assembly power tools, and railway power tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators, and electric planers, etc. The electronic device includes the aforementioned lithium-ion battery, and therefore the advantages of including the aforementioned lithium-ion battery are not elaborated here.

[0059] In summary, this invention proposes a lithium-ion battery electrolyte and its application. By introducing a soluble single-ion conductor additive into the electrolyte, the lithium-ion transport number can be increased, enhancing the lithium-ion transport capacity and significantly reducing lithium-ion concentration polarization on the negative electrode surface, effectively alleviating the lithium deposition problem on the negative electrode surface during fast charging. The single-ion conductor additive forms a stable solid electrolyte interface film on the negative electrode surface, promoting the desolvation process of lithium ions, improving the battery's fast charging and rate performance, and effectively solving the problem of balancing fast charging capability and high-temperature performance. The film-forming additive can suppress the occurrence of side reactions on the electrode surface, increase the initial discharge capacity of the lithium-ion battery, improve the high and low temperature storage performance of the lithium-ion battery, and enhance the high-temperature cycle performance of the lithium-ion battery.

[0060] The above description is merely a preferred embodiment of this application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in this application is not limited to the technical solutions formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept. For example, technical solutions formed by replacing the above-mentioned features with technical features with similar functions disclosed in this application (but not limited to) each other.

[0061] Apart from the technical features described in the specification, the other technical features are known to those skilled in the art. To highlight the innovative features of this invention, the other technical features will not be described in detail here.

Claims

1. A lithium-ion battery electrolyte, characterized in that, It includes at least the following components: Non-aqueous solvents; Lithium salts; as well as Additives, including single-ion conductor additives, wherein the general structural formula of the single-ion conductor additives is: Wherein, n=10~100; the mass content of the single-ion conductor additive in the electrolyte is 0.05%-3%.

2. The lithium-ion battery electrolyte according to claim 1, characterized in that, The additives also include film-forming additives, which include one or a combination of at least two of vinyl sulfate, 1,3-propanesulfonate lactone, vinylene carbonate, fluoroethylene carbonate, or ethylene ethylene carbonate.

3. The lithium-ion battery electrolyte according to claim 2, characterized in that, The film-forming additive has a mass content of 0.5%-2% in the electrolyte.

4. The lithium-ion battery electrolyte according to claim 2, characterized in that, The film-forming additives include vinyl sulfate and 1,3-propanesulfonate lactone.

5. The lithium-ion battery electrolyte according to claim 1, characterized in that, The lithium salt is selected from any one or a combination of at least two of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalate)borate, lithium difluorobis(oxalate)phosphate, lithium difluorophosphate, or lithium trifluoromethanesulfonate.

6. The lithium-ion battery electrolyte according to claim 1, characterized in that, The lithium salt has a mass content of 8%-18% in the electrolyte.

7. The lithium-ion battery electrolyte according to claim 1, characterized in that, The non-aqueous solvent includes any one or a combination of at least two of ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, or diethyl carbonate, and the mass content of the non-aqueous solvent in the electrolyte is 60%-85%.

8. A lithium-ion battery, characterized in that, Includes the lithium-ion battery electrolyte as described in any one of claims 1-7.

9. An electronic device, characterized in that, Including the lithium-ion battery as described in claim 8.

Citation Information

Patent Citations

  • A composite diaphrag and a preparation method thereof

    CN109585750A

  • Electrode for secondary battery and method for making same, and secondary battery using this electrode

    JP2008235249A